STRATEGI PENGEMBANGAN POTENSI WILAYAH SEBAGAI UPAYA PEMERATAAN PEMBANGUNAN DI KABUPATEN JAYAWIJAYA - Normalia Ode Yanthy; Anggia R Nurmangtyas (DINAMIS, 2014)
Activities development of Jayawijaya Regency so far only focused on one area, inDistrict of Wamena Kota. This causes spatial disparity of development in the Regencyof Jayawijaya. This study aims to identify the potential and the problems that can affectthe distribution of development equitable, also formulate strategies developmentequitable in Jayawijaya .The method in this study are : (i) the approach used is a combination ofmodels/sequential explanatory design, (ii) LQ and SWOT analysis.. The results ofanalysis LQ showed Jayawijaya has 5 economic sectors bases, namely sector : (1)agriculture, (2) bulding, (3) trade, hotels and restaurants, (4) finance, leasing, andbusiness services, (5) services. Based on the results of SWOT analysis, there are 4strategies development equitable in Jayawijaya : (1) improving facilities andinfrastructure supporting comparative economic sectors, (2) improve socialization ortraining programs to the community in order to increase community skills, particularly inagriculture and tourism activities, (3) developing a data base of agricultural and tourismpotential, devoted to the promotion of the importance of tourism activities in theRegency Jayawijaya and expansion of agriculture and tourism market, and (4) expandtheir territory based on potential/comparative advantage they have.